Evaluation of the benefits of functional endoscopic sinus surgery on bronchial asthma in patients with concomitant nasal polyposis - Gupta, Vijay; Gupta, Arindam (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
Background: It is important to understand the relationship between diseases of the upper and lower respiratory tracts because of the prevalence of nasal polyp and asthma, their impact on patients’ lives, the resultant burden on the health care system, and the potential benefits of functional endoscopic sinus surgery. Objective of the study was to evaluate the benefits of functional endoscopic sinus surgery (FESS) on bronchial asthma in patients with concomitant nasal polyposis. Methods: A total of 30 patients having nasal polyposis with asthma were taken up in the study. Patients were evaluated in reference to radiographic study of nose and PNS, pulmonary function by spirometry and asthma symptoms by ACT score. FESS was performed in all patients. Post-surgery spirometry and ACT score was done at 3 and 6 months. Results: Maximum patients belonged to the age group of 35-49 years. When compared pre and post-operative ACT score, we observed a mean of 15.7 (pre-operative), 13.6 (at 3 months) and 19.8 (at 6 months). FEV1% score was 74.6 pre-operatively, which was 90.2% at 3 months and 95.5% at 6 months of follow up. Conclusions: FESS has a positive influence in the lower airways function of asthmatic patients. Recorded improvement of the subjective and objective parameters measured, should not only be attributed to alleviation of upper airway symptoms and to concomitant improvement of a patient’s quality of life, but also to the positive influence of FESS on the intrinsic mechanisms.